4H–SiC Avalanche Photodiode Linear Array Operating in Geiger Mode - Lianghui Li; Dong Zhou; Hai Lu; Wenkai Liu; Xiaofan Mo; Fangfang Ren; Dunjun Chen; Ruiqi Wang; Guanglei Li; Rong Zhang; Youdou Zheng (IEEE Photonics Journal, 2017)
In this study, a 50-pixel linear array of 4H–SiC ultraviolet avalanche photodiodes operating in Geiger mode is reported for the first time. The 50 pixels within the linear array are all capable of detecting single photons but with a small number of them suffering from extra leakage current near avalanche breakdown. The enhanced leakage is likely correlated with structural defects existing within the epitaxial structure, which would lead to higher dark count rate (DCR) at the same single photon detection efficiency (SPDE) in Geiger mode. For a low-leakage avalanche photodiode device within the linear array, a room temperature SPDE of 15.4% at 280 nm is obtained with a corresponding DCR of 2.5 Hz/μm2.